Associations Between Self-Control, Practice, and Skill Level in Sport Expertise Development. Issue 1 (2nd January 2017) - Tedesqui, Rafael A. B.; Young, Bradley W.
Abstract : Purpose: The purpose of this study was to test the association between self-control (SC) variables and (a) sport-specific practice amounts, (b) engagement in various practice contexts, (c) threats to commitment to one's sport, and (d) skill development using the Brief Self-Control Scale (BSCS) in a diverse sport sample.Method: Two hundred forty-four athletes (47% female; M age = 21.96 years, SD = 6.98 years; 68.8% individual sports and 31.2% team sports; 13.77 [ SD = 8.12] hr/week of sport-specific practice) completed a survey composed of the BSCS and practice-related measures. Three skill groups (basic/intermediate, advanced, expert) were informed by athletes' self-reported highest level of competition. Separate analyses were conducted for juniors (aged 12–17 years) and seniors (aged 18–43 years).Results: A 2-factor model (self-discipline and impulse control) fit the BSCS data. Fewer thoughts of quitting from one's sport were associated with higher self-discipline in juniors and seniors and were also related to higher impulse control in seniors. Greater practice amounts were associated with higher self-discipline; however, only seniors showed such associations in voluntary practice contexts. For juniors and seniors, impulse control was associated with more voluntary practicing. There were, however, no skill-group differences for levels of self-discipline or impulse control.Conclusions: Self-discipline and impulse control may be dispositional characteristics associated with how athletes engage in practice and avert conditions that threaten their sport commitment. SC dispositions may relate to practice amounts differently in juniors and seniors, depending on the requirements for self-regulation in a practice context.